1991
DOI: 10.1113/jphysiol.1991.sp018619
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of lamb intestinal digestive enzymes is not regulated by diet.

Abstract: SUMMARY1. Change in digestive enzyme activities determined biochemically in brushborder membrane vesicles and cytochemically in isolated villi of lamb proximal intestine has been related to diet, intestinal structure and rumen development during the first 10 weeks of postnatal life.2. Lactase activity halved, dipeptidylpeptidase IV activity doubled and aminopeptidase N and alkaline phosphatase activities remained constant during this period of development. Maintaining lambs on a milk replacer diet for 5 weeks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…Maltase is expressed all along the equine small intestine. Maltase activity is similar in proximal, mid and distal regions and is extremely high compared with other species; 1 µmol/min/mg protein in the horse (this study) vs. 0.013-0.054 µmol/min/mg wet weight tissue in man (Dahlqvist 1964;Dyer et al 1997b) and 0.014 µmol/min/mg protein in sheep (Shirazi-Beechey et al 1989, 1991b. T h e brush-border membrane lactase is the enzyme responsible for the breakdown of the milk sugar, lactose.…”
Section: Discussionmentioning
confidence: 84%
“…Maltase is expressed all along the equine small intestine. Maltase activity is similar in proximal, mid and distal regions and is extremely high compared with other species; 1 µmol/min/mg protein in the horse (this study) vs. 0.013-0.054 µmol/min/mg wet weight tissue in man (Dahlqvist 1964;Dyer et al 1997b) and 0.014 µmol/min/mg protein in sheep (Shirazi-Beechey et al 1989, 1991b. T h e brush-border membrane lactase is the enzyme responsible for the breakdown of the milk sugar, lactose.…”
Section: Discussionmentioning
confidence: 84%
“…The increase in transporter protein was closely related to increasing site density in the BBM from lamb [27]. With age, the function of absorbing nutrients such as amino acids and glucose in the proximal intestine was impaired in aged mice [9].…”
Section: Discussionmentioning
confidence: 91%
“…G␣ gust and T1R3 knockout mice had similar amounts of intestinal SGLT1 protein and Na ϩ -dependent glucose transport when maintained on low-or high-carbohydrate diets. Thus, whereas wild-type animals are known to respond to increased dietary carbohydrate with enhanced SGLT1 expression (4,15), neither G␣ gust nor T1R3 knockouts responded in this way. Morphometric analysis indicated that neither crypt depths nor villus heights differed in the intestines of mice maintained on either a low-or a high-carbohydrate diet, ruling out a trophic effect [see supporting information (SI) Fig.…”
Section: Regulation Of Intestinal Sglt1 Expression In Wild-type and Kmentioning
confidence: 99%
“…Total RNA isolated from intestinal tissue by using the RNeasy Mini Kit with on-column DNase 1 digestion (Qiagen, Crawley, U.K.) was used for cDNA synthesis using Superscript III reverse transcriptase (Invitrogen, Carlsbad, CA) and oligo(dT) [12][13][14][15][16][17][18] primers. cDNA was cleaned up by using the Machery-Nagel Nucleospin extract kit (AB Gene, Epsom, U.K.), and 50 ng of cDNA was used per reaction.…”
Section: Methodsmentioning
confidence: 99%